A photonic pH sensor based on photothermal spectroscopy - Hartings, Matthew R. (Sens Actuators B Chem, 2019)
Although the determination of pH is a standard laboratory measurement, new techniques capable of measuring pH are being developed to facilitate modern technological advances. Bio-industrial processing, tissue engineering, and intracellular environments impose unique measurement requirements on probes of pH. We describe a fiber optic-based platform, which measures the heat released by chromophores upon absorption of light. The optical fibers feature fiber Bragg gratings (FBG) whose Bragg peak redshifts with increasing temperature. Using anthocyanins (pH-sensitive chromophores found in many plants), we are able to correlate visible light absorption by a solution of anthocyanins to heat released and changes in FBG signal over a pH range of 2.5 to 10. We tested the ability of this platform to act as a sensor coating the fiber within a layer of crosslinked polyethylene glycol diacrylate (PEG-DA). Incorporating the anthocyanins into the PEG, we find that the signal magnitude increases over the observed signal at the same pH in solution. Our results indicate that this platform is viable for assessing pH in biological samples and point at ways to optimize performance.